Control Strategy Assessment: PID and Fuzzy-PID for Compound DC Motor Systems - Yaw Amankrah Sam-Okyere; Emmanuel Osei-Kwame; Dienatu Issaka; Isaac Papa Kwesi Arkorful (MSD Institute, 2025)
Compound DC motors, prized for their high torque and speed in industrial applications, demand robust control under nonlinear conditions. This study advances the field of Adaptive Neuro-Fuzzy Interface (ANFIS) by comparing a Ziegler-Nichols-tuned Proportional-Integral-Derivative (PID) controller with a novel ANFIS-PID controller for a compound DC motor. Unlike prior work, the research focuses on the unique dynamics of compound motors for real-time applications. Using MATLAB Simulink simulations. Performance was assessed via overshoot, rise time, settling time, and steady-state error under no-load and full-load conditions. The PID controller yielded 11.789% overshoot, 1.140s rise time, and 2.251s settling time, while the ANFIS-PID achieved 6.989% overshoot, 0.951s rise time, and 1.962s settling time, with a 50% lower steady-state error. These results, validated across 10 runs (p < 0.05), highlight the ANFIS-PID’s superior adaptability to the motor’s series-shunt dynamics, offering a 40.7% overshoot reduction.